2014
DOI: 10.1093/femsec/fiu025
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal community diversity and abundance changes along a natural salinity gradient in estuarine sediments

Abstract: Archaea are widespread in marine sediments, but their occurrence and relationship with natural salinity gradients in estuarine sediments is not well understood. This study investigated the abundance and diversity of Archaea in sediments at three sites [Brightlingsea (BR), Alresford (AR) and Hythe (HY)] along the Colne Estuary, using quantitative real-time PCR (qPCR) of 16S rRNA genes, DNA hybridization, Archaea 16S rRNA and mcrA gene phylogenetic analyses. Total archaeal 16S rRNA abundance in sediments were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 109 publications
10
53
0
2
Order By: Relevance
“…Methanosarcinales and Methanomicrobiales were the most abundant Euryarchaeota groups in freshwater sediments, and both methanogenic and methanotrophic phylotypes (ANME-2a, 2b) were included [15]. The dominance of Methanomicrobiales and Methanosarcinales in sedimental archaea community of this study was not a single event, and similar results have also been reported in other freshwater lakes, such as Lake Biwa [41], Lake Soyang [42], and Lake Dagow [43].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Methanosarcinales and Methanomicrobiales were the most abundant Euryarchaeota groups in freshwater sediments, and both methanogenic and methanotrophic phylotypes (ANME-2a, 2b) were included [15]. The dominance of Methanomicrobiales and Methanosarcinales in sedimental archaea community of this study was not a single event, and similar results have also been reported in other freshwater lakes, such as Lake Biwa [41], Lake Soyang [42], and Lake Dagow [43].…”
Section: Discussionsupporting
confidence: 83%
“…Archaea community is less influenced by environmental factors compared with bacteria [13]; several parameters are found to affect the distribution of archaea in lake sediments. The salinity played an important role in controlling diversity and distribution of archaea in estuarine sediments [14, 15], particle sizes and water O 2 saturation also shaped the sediment archaea distribution [16]. However, subject to the poor culturability and limited isolates of archaea members, the taxonomy was obscured in many previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations are consistent with reports showing predominance of the same taxa of bacteria in large brackish environments (Riemann et al, 2008), in estuaries and coastal saline gradients (Campbell et al, 2011;Herlemann et al, 2011;Fortunato et al, 2012;Fortunato and Crump, 2015), and in polar surface waters (Zeng et al, 2009;Teske et al, 2011;Prasad et al, 2014;Signori et al, 2014;Piquet et al, 2015) and Patagonian glacial fjords (Gutiérrez et al, 2015). For archaeal OTUs, predominance of members of the phylum Thaumarchaeota (including Marine group I Archaea) is consistent with this group being a major contributor to microbial diversity in estuarine waters and sediments (Webster et al, 2015;Xia et al, 2015), in polar waters (Bano et al, 2004;Galand et al, 2008Galand et al, , 2009a, in sea ice (Collins et al, 2010;Cowie et al, 2011) and in fjord environments (Zaikova et al, 2010;Gutiérrez et al, 2015). Regarding Thermoplasmata, most sequences were affiliated to the uncultured Marine group II, which represents a significant fraction of the archaeal community in estuarine waters (Xia et al, 2015) and coastal waters of the Arctic Ocean (Galand et al, 2008(Galand et al, , 2009a, but in fjords appear to be poorly represented (Zaikova et al, 2010).…”
Section: Community Composition Of Prokaryotes In Water Masses Of Puyusupporting
confidence: 92%
“…The archaeal abundance of wet samples was comparable with the reported abundances in similar habitats like pond sediments (Brandt et al 2014), rich fen (Petersen et al 2012), and estuarine sediments (Webster et al 2015). By contrast, those of the dry samples (1.4 × 10 8 to 2.4 × 10 9 copies (g d.w.s.)…”
Section: Increase Of Archaeal Abundance After Water Floodingsupporting
confidence: 78%